Human Resource Management Based on Islamic Values: Strengthening Employee Welfare in Educational Institutions - Aslinda, Aslinda; D, Dasrizal; Elhusen, Shofwan Karim (Ruhama : Islamic Education Journal, 2024)
This research investigates strategies, methods, and scientific facilities in the development of science. Its main focus lies in identifying effective strategies that enhance scientific progress, including interdisciplinary collaboration, investment in research infrastructure, and the application of information technology. The research methods employed include qualitative data analysis derived from scientific literature and field research. The findings highlight the importance of interdisciplinary collaboration in addressing the complexity of contemporary scientific challenges. Evaluation is also conducted on the effectiveness of research methods in generating new knowledge and enhancing scientific understanding. Furthermore, this study identifies the crucial role of scientific facilities such as software, laboratory equipment, and access to databases in supporting scientific advancement. The results offer valuable insights for scientific policy development, emphasizing the need for investment in state-of-the-art research infrastructure and greater support for interdisciplinary collaboration. In conclusion, this research provides a significant contribution to the understanding of how to strengthen strategies, methods, and means of developing science to advance knowledge and innovation in various scientific fields.Keyword; strategies; method; facility; sciences